DEVELOPMENT OF POWTOON APPLICATION-BASED LEARNING MEDIA FOR XI IPS CLASS STUDENTS IN TUGUMULYO STATE HIGH SCHOOL - Adha Subali, Rifqi Galih; Supriyanto, Supriyanto; Susilo, Agus (Universitas Labuhanbatu, 2024)
This study aims to develop and produce powtoon application-based history learning media that are valid, practical, and effective in learning History class XI IPS at SMA Negeri Tugumulyo. This research uses a Research and Development approach with the application of the ADDIE model. The research subjects consisted of 3 validation experts, 1 history subject teacher, and 34 students of XI IPS 2 class at SMA Negeri Tugumulyo. Data collection techniques included observation, interviews, questionnaires, tests, and documentation. The results of the expert assessment analysis showed that the powtoon application-based history learning media met the validity criteria, with a percentage of 86% linguist assessment, 92% material expert, and 77% media expert. In addition, the results of the practicality sheet assessment from teachers and students showed that the media also met the practical criteria, with an average practicality score of 88%. While the large group test shows that the learning media has high effectiveness, with an N-gain (g) value of 0.72, which is classified as high. Thus, it can be concluded that the powtoon application-based history learning media proved to be valid, practical, and effective in the context of History learning class XI IPS 2 at SMA Negeri Tugumulyo.